1997
DOI: 10.1159/000201443
|View full text |Cite
|
Sign up to set email alerts
|

Acute Hepatic Failure following Transcatheter Arterial Embolization for the Treatment of Hepatocellular Carcinoma

Abstract: We conducted a retrospective analysis to evaluate the risk factors associated with the occurrence of acute hepatic failure following transcatheter arterial embolization (TAE) for hepatocellular carcinoma. From 1984 to 1993 we performed a total of 623 embolization procedures in 369 patients with both hepatocellular carcinoma and chronic liver disease. Within 2 weeks after TAE, 13 patients (2.1%) experienced hepatic failure as characterized by a rapid increase in serum bilirubin levels and the development of hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…21 In this study, we found that patients with post-TACE hepatic failure had a 2.13-fold increased risk of mortality in the Cox model in comparison with patients without hepatic failure among patients with preexisting ascites receiving TACE. Notably, in this subset of patients, 94% of 17 patients with the development of liver failure died within 1 year of TACE treatment.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…21 In this study, we found that patients with post-TACE hepatic failure had a 2.13-fold increased risk of mortality in the Cox model in comparison with patients without hepatic failure among patients with preexisting ascites receiving TACE. Notably, in this subset of patients, 94% of 17 patients with the development of liver failure died within 1 year of TACE treatment.…”
Section: Discussionmentioning
confidence: 55%
“…In this study, strikingly, we found that 98 patients with HCC had ascites before TACE and 17 (17.3%) of them developed liver failure after treatment; the incidence of liver failure is higher than those in the reports from other studies. 17,20,21,25 Our results clearly indicate that patients with HCC and ascites are at a substantially higher risk of developing post-TACE liver failure.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Using combined TAE and PEI in the treatment of large HCCs (n = 83), Tanaka et al [52] yielded 35% of 5-year survival. TACE therapy is facing two major problems: TACE increased the risk of pulmonary metastasis, and acute hepatic failure (2.1% in 369 patients) was also reported following TACE [53,54].…”
Section: Transcatheter Arterial Chemoembolizationmentioning
confidence: 99%
“…Contrast associated nephropathy requiring dialysis is rare. Transarterial chemoembolisation (TACE) may also induce nephropathy and, previously, we reported that 1% of patients with hepatocellular carcinoma may develop acute renal failure following TACE [4]. Renal cortical retention (RCR), of contrast medium was suggested as a sign of renal deficiency following the use of contrast medium [5][6].…”
mentioning
confidence: 99%